On our com(mon)passions: Entanglements of research, teaching practices, and institutional lives - García-González, Macarena; Deszcz-Tryhubczak, Justyna (Critical Studies in Teaching and Learning, 2023)
This article takes the form of a conversation between two children’s literature scholars who are collaborating on a conceptual and methodological exploration of post-humanist and feminist materialist concepts and ideas in their field. They reflect on how this exploration has reshaped not only their research and methodological approaches but also their institutional lives in Higher Education. The authors also relate to the propositions for slow scholarship and response-able pedagogies, reflecting on their teaching practices and the mentoring of master and PhD students in their different geographical and institutional backgrounds, among other dimensions of what they call their ‘institutional selves’. Departing from Olga Cielemęcka and Monika RogowskaStangret’s (2015) concept of “com(mon)passions”, the authors propose a deeper engagement in the entanglements of thinking/feeling, teaching/learning, and critical/creative as continuums that may open spaces for (new) modes of knowledge production that resist the pressure of neoliberal and positivist academia.